Pre-purchase behaviour: Is there a cognitive dissonance? - Gan, Chin Chuan *; Ding, Hooi Ting (AENSI Publisher, 2014)
The purpose of the study is to provide a better understanding of pre-decisional conflict between different states of buyers. The focus of the study is on the uncertainty; ambiguity, similarity, and overloaded uncertainty that induce post-decisional conflicts. On top of that, the researchers also analysed the mediating effects between the dependent and independent variables using Structural Equation Modelling (SEM) in Malaysia within the context of computer purchase experience. The findings show that ambiguity uncertainty is an important antecedent to emotional and wisdom of purchase conflict state after their purchase decision. Whereas, overloaded and similarity uncertainty was found to indirectly effect both types of post-decisional conflict but indirectly effect through ambiguity uncertainty.